Innovations for equity: how to untap the gender-transformative potential of innovations in the agri-food sector - Basu, Sharmishtha; Kawarazuka, Nozomi; Khan, Suhela; Reddy, C.S.; Burg, Margreet van der (Deutsche Gesellschaft für Internationale Zusammenarbeit, 2023)
Since 2021, the GIZ Fund for the Promotion of Innovation in Agriculture (i4Ag) promotes cross-cutting innovations that contribute to a climate-resilient transformation of the agri-food sector. Innovations are understood to introduce new practices or change existing ones. Moreover, innovations are understood to be inherently gendered in nature. Hence, in order to ensure maximum benefit, i4Ag addresses gender aspects in the design, implementation and evaluation of innovations. Drawing on the experience of implementing innovations at the nexus of rice cultivation and climate action in South Asia, this panel session will bring together practitioners and international experts from research and policy. Considering the opportunities and challenges of gender-responsive innovations in the field, the panel will discuss and reflect on entry points and strategies to raise the level of ambition and to untap the gender-transformative potential of innovations in the agri-food sector. In doing so, this panel session will link insights from project implementation to wider critical debates on the transformation of agri-food systems and the role of feminist development policy. Contributing organizations/panellists: GIZ (TBD); University of Wageningen (Margreet van der Burg); UN Women (Suhela Khan); CIP (Nozomi Kawarazuka, TBC) and OLAM (TBD).